POLITIK PEMBERITAAN DALAM KASUS KORUPSI PETINGGI PARTAI POLITIK (Analisis Isi Berita Kasus Korupsi Luthfi Hasan Ishaaq, Anas Urbaningrum, dan Ratu Atut Chosiyah pada Koran Tempo, Kompas, dan Republika) - Iswandi Syahputra (Profetik: Jurnal Komunikasi, 2014)
Corruption involving officials of political parties occurred during the year 2013 to get the most attention from the media. Among those cases, cases involving Anas Urbaningrum (Democrat Party), Lutfi Hasan Ishaaq (Social Welfare Party), and Ratu Atut Choisyah (Golkar Party) gets more attention. Not only because of the amount of cases that involve him, but also with regard to their position in the party respectively. The mass media has a point of view of each, which is called by the political news. Political news, consciously or not, the media made the construction of each in light of a case, including the reporting of corruption cases involving officials of political parties in Indonesia.This study aimed to determine: (1) How the news media tendency toward corruption case involving three political party officials (Lutfi Hasan Ishaaq, Anas Urbaningrum, and Ratu Atut Chosiyah)? And, (2) How the construction of reality that is built up of news about third parties which officials are involved in corruption cases? By using the content analysis method, the results showed, in the third news media, Koran Tempo, Kompas, nor Republika, the news media about the third third corruption case involving the three leaders of political parties, if the terms of journalistic work procedures, it appears that elements of prominence become the main dish in the news. The three media have also made a good construction on the dangers of corruption, however, should be aware that the news media is not used for political purposes.